Analisis Perbandingan Tingkat Pengembalian (Return) Saham Syariah Dan Saham Konvensional Yang Aktif Dan Tercatat Di Bursa Efek Indonesia - M. Rizqon Al Musafiri (Jurnal Istiqro, 2018)
A lot of alternative investing. Ranging from real assets to securities investments, ranging from a conventional manifold to the manifold sharia. But the main choice of someone in investing is how the return offered to how risk that may occur. And stocks in LQ45 is a collection of existing liquid shares on the Stock Exchange and JII also a collection of shares that have good performance in the category of sharia. Islamic and conventional stock returns are something that needs to be known primarily for Islamic investors. Then how it compares with a return of Islamic stocks of conventional stock. It can be analyzed via the stock's annual return and standard deviation as a risk by using T test Test Independent. Then obtained 15 samples of Islamic stocks and 15 samples of conventional stock and annual data taken stock price during the period January 2014 to 2015. The results showed that there are significant differences from the comparison of income received in shares of income received conventional with conventional stock for p value of <0.05. This shows that Ho is rejected and HI accepted because p value = 0048> 0.05 in accordance with the principle of investing High Risk High Return, Low Risk Low Return where the higher the risk the higher the market rate / return and conversely the smaller the risk of getting Similarly small rate of return. Therefore, investors in Indonesia must be careful in making a good investment in the shares of conventional and Islamic stock in order not to experience a capital loss.